Pelatihan Tari Kreasi Jaipongan Sebagai Strategi Pelestarian Budaya Lokal Melalui Kegiatan Ekstrakurikuler Di SMA Negeri 1 Ciamis - Hervista, Ghea Andriany (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to enhance students' understanding and skills in traditional dance through Jaipongan creative dance training as an effort to preserve local culture within the school environment. Based on initial observations, the majority of students had never received direct training in traditional dance and had limited understanding of the characteristics of Jaipongan dance. This research employs a Participatory Action Research approach a collaborative method that actively involves researchers, supervising teachers, and students in the processes of planning, action, observation, and reflection. The training process was participatively adapted to the students’ needs and responses over a four-week implementation period. The training materials included the introduction of basic Jaipongan movements, rhythm and floor pattern exercises, expression, and group choreography development. Evaluation results showed that out of 25 participating students, 13 students (52%) achieved the “excellent” category, 4 students (16%) were in the “good” category, while the rest still required further guidance. The training not only improved technical skills but also fostered appreciative attitudes, cooperation, and self-confidence. Through the PAR approach, students were not merely objects of learning but also active subjects, encouraging the process of cultural arts education to become more contextual, reflective, and transformative.